HOLISTICS JOURNAL HOLISTICS JOURNAL HOSPITALITY AND LINGUISTICS: Exploring Web-Based Resources on Communication Practices: A Breakthrough in English for Hospitality Industry - Beni Wijaya (HOLISTICS, 2021)
Insofar as communication skills in the hospitality industry remain a major concern in the workplace, a breakthrough is highly paramount and sought-after regarding the barriers in English. Barely in industrial career have the people been equipped with adequate English instructional materials for communication practices. The workplace climate thereby tends to be less enthralling and humdrum. To address this pertinent issue, the internet offers a wide array of invaluable information sources to shape the way out through the World Wide Web. Web-based resources have presently been a prevalent upshot from the recent digital literacy due to the covid-19 pandemic. Accordingly, this paper aims to shed new light on the use of web-based resources to better facilitate communication practices in English for the hospitality industry. The useful websites are put forward regarding some domains in the industry. It is necessarily suggested that those in the related sector be able to take advantage of the proposed information.